A systematic review on the complications and management of hepatic adenomas: a call for a new approach. Issue 8 (August 2020) - Rodrigues, Beverly T.; Mei, Swee Lin Chen Yi; Fox, Adrian; Lubel, John S.; Nicoll, Amanda J.
Abstract : Hepatic adenomas are benign hepatic lesions with heterogeneous characteristics. Awareness of complications, including haemorrhage and malignant transformation, has improved alongside a concurrent rise in their detection. Monitoring and management guidelines, however, remain inconsistent. This systematic review analyses the natural history of hepatic adenomas, and existing and novel risk factors associated with haemorrhage and malignant transformation. Results of this systematic review commonly identified male sex, and the beta-catenin histopathological hepatic adenoma subtype, as risk factors for malignant transformation, whilst those associated with haemorrhage included lesion size and number, exophytic nature, and recent hormone use. Overall, females demonstrated higher rates of haemorrhage, whilst males exhibited a higher risk of hepatocellular carcinoma development. This systematic review highlights that tumour size and subtype may not be as characteristically linked with complications as previously thought. We have additionally reported novel risk factors contributing to development of hepatic adenoma-related complications. We conclude by highlighting the risk of taking a conservative approach to seemingly low-risk lesions and suggest revised practice guidelines.